(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted on Sidr trees, apple variety, at the age of 10 years, planted in one of the private orchards in Al-Hartha area in Basra governorate, for the purpose of determining the date of emergence of cracking and changes in some anatomical characteristics of healthy and cracked fruits during growth and ripening.The results showed that crack formation occurred in the pericarp tissue 31 days after full flowering and continued to develop during the growth stages until the fruits affected by this damage reached the stage of maturity. The results also showed that there were significant differences in some anatomical characteristics of healthy and cracked fruit tissues. Significantly healthy on cracked fruits in the thickness of cuticle and cuticle layers and the number of cells per mm2 of the inner mesocarp tissue were recorded.